(untitled) (Journal of Science and Technology, 2016)
A 13-year survey of paralytic poliomyelitis was carried out in Komfo Anokye Teaching Hospital which is situated in a tropical rain forest. The diagnosis was made clinically. One thousand one hundred and sixty-four cases of paralytic polio were recorded during the period of 13 years. The disease was found to be seasonal with lune-October as the peak months. Children between 1 -2 years formed 57.7% of all the cases of paralytic polio and 95.5% involved children under 5 years. The younger the child the more readily it developed paralysis after injections. Although chloroquine was the commonest drug injected (78%) antibiotics and DPT vaccines also provoked paralysis. The death rate was found to be 3.1%. After physiotherapy 68% of the cases recovered from the paralysis. the remaining 32% involving children who had multiple injections had to use either callipers or clutches. Injections may have played an important role in provoking paralytic poliomyelitis in this survey. Unnecessary injections should therefore be avoided. The tremendous decline of paralytic potboiler 1980 in the survey is definitely due to the improved vaccination programme, which should further be intensified to completely eradicate this handicapping disease.